Flexibility Production and Policy Credit Trading : Overview Theoretical to Influence Uncertainty Demand and Competition Among Suppliers - Ngadi Permana; Muhammad Faiz Yasir (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review explores the impact of production flexibility on trade credit policy in the context of demand uncertainty and supplier competition. The findings show that production flexibility significantly affects the value and maturity of trade credit. Flexible firms tend to delay defaults, order larger quantities, and receive higher trade credit values. This flexibility allows firms to adjust their production capacity according to market changes, increasing their bargaining power in trade credit negotiations. In addition, production flexibility influences firms’ capital structure decisions and financial flexibility, which have a positive impact on trade credit policy. However, the proportion of trade credit to firm value is higher in less flexible firms. Although providing valuable insights, this study is limited by the existing literature and lacks empirical validation. Future research should test these findings empirically and explore industry-specific factors.